Human development : Multi Dimensional Approach to Human Well-being - Sengupta, Keya; Sengupta, Keya, 1957- (New Delhi : Concept Pub. Co, 2010)
Contributed articles.
Includes bibliographical references and index.
Keywords: Human capital -- India